The influence of carbon emission disclosure on financial performance: Do firm characteristics matter? - Lina, Lina; Adelia, Firdha (Jurnal Akuntansi dan Auditing Indonesia, 2024)
This study aims to provide empirical evidence on the effect of carbon emission disclosure on financial performance by considering the moderating role of firm characteristics, such as firm size, firm age, and sales growth. This quantitative study is based on the positivism paradigm that applies the purposive sampling method in determining its sample. Hypothesis testing uses multiple regression and moderated regression analysis. This study successfully proves that carbon emission disclosure has a positive effect on accounting-based performance measures. This positive effect can only be strengthened by one of the firm characteristics tested in this study, sales growth. Meanwhile, this study has not succeeded in proving the positive effect of carbon emission disclosure on market-based performance measures. This study contributes to the development of literature, especially carbon emission disclosure research, by proving signaling theory and legitimacy theory. This study has practical implications, especially for Indonesia and China, related to the issue of carbon emission disclosure. This study offers novelty in carbon emission disclosure research by introducing new moderators, firm characteristics and focusing on energy sector companies in Indonesia and China.